2019
DOI: 10.33401/fujma.409748
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inflation on Stochastic Optimal Investment Strategies for DC Pension under the Affine Interest Rate Model

Abstract: In this paper, we seek to investigate the effect of inflation on the optimal investment strategies for DC Pension. Our model permits the plan member to make a defined contribution, as provided in the Nigerian Pension Reform Act of 2004. The plan member is free to invest in risk-free asset and two risky assets. A stochastic differential equation of the pension wealth that takes into account certainly agreed proportions of the plan member's salary, paid as a contribution towards the pension fund, is presented. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Also, Sani et al (2022) found a negative and statistically significant link between inflation and pension contributions in the long and short. Similarly, Njoku and Osu (2019) reported that inflation has a significantly negative effect on the optimal investment strategy of pension plans. Estrada et al (2017) argued that inflation strongly affects any pension system in the long run (Estrada et al, 2017).…”
Section: The Moderating Role Of Inflationmentioning
confidence: 99%
“…Also, Sani et al (2022) found a negative and statistically significant link between inflation and pension contributions in the long and short. Similarly, Njoku and Osu (2019) reported that inflation has a significantly negative effect on the optimal investment strategy of pension plans. Estrada et al (2017) argued that inflation strongly affects any pension system in the long run (Estrada et al, 2017).…”
Section: The Moderating Role Of Inflationmentioning
confidence: 99%